Cardioprotective Activity of Costus Root Ethanol Extract in Experimentally-Induced Hypothyroidism in Female Albino Rats - Mohammed Rashed Abdul; Saleh Mohammed Rahim; Ahmad Hamad Saleh (HAYATI Journal of Biosciences, 2023)
Hypothyroidism is a popular endocrine disorder caused by a thyroid hormone deficit. Changes in the state of the thyroid gland significantly affect many organs, including the heart. This study examined the cardioprotective effects of an artificially induced hypothyroidism in female rats using an ethanol extract from the root plant Saussurea lappa (Costus). For the current study, 25 adult female albino rats were employed. They were split into five equal groups, including control, hypothyroid group, post-treatment group with costus extract, co-administered hypothyroid group with costus extract, and post-treatment group with levothyroxine. Thyroid hormones (T3, T4, and TSH), lipid profile, and oxidative stress indicators (catalase, superoxide dismutase, reduced glutathione, and lipid peroxidation levels) were also measured in the serum. The heart muscle was the subject of a histological research. The findings suggested that Costus root ethanol extract improved hypothyroidism in female rats, as proven by the reversal of many biochemical abnormalities and improvements in the heart's histology. Our study indicates that the root of Costus exhibited cardioprotection efficiency against hypothyroidism-induced serious effects on the heart, The antioxidant and radical-scavenging properties of its components may be responsible for this promising effect.